2021
DOI: 10.1007/s10557-021-07263-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Statin Therapy in Patients with Hospital Admission for COVID-19

Abstract: Purpose COVID-19 is characterized by dysfunctional immune responses and metabolic derangements, which in some, lead to multi-organ failure and death. Statins are foundational lipid-lowering therapeutics for cardiovascular disease and also possess beneficial immune-modulating properties. Because of these immune-modulating properties, some have suggested their use in COVID-19. We sought to investigate the association between statin use and mortality in patients hospitalized with COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
1
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 41 publications
1
17
1
4
Order By: Relevance
“…In total, 36 of 49 studies (73%) show a lower risk of severe COVID‐19 outcomes––in particular mortality––among statin users compared with nonusers. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 In 11 studies, ratio measures were close to 1. 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 In 2 studies, an increased risk was observed.…”
mentioning
confidence: 95%
“…In total, 36 of 49 studies (73%) show a lower risk of severe COVID‐19 outcomes––in particular mortality––among statin users compared with nonusers. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 In 11 studies, ratio measures were close to 1. 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 In 2 studies, an increased risk was observed.…”
mentioning
confidence: 95%
“…En primer lugar, nos gustaría destacar que las notables diferencias en cuanto a las características clínicas basales que presentaban los pacientes hospitalizados con COVID-19 que recibían tratamiento previo con estatinas en relación a aquellos que no recibían estos fármacos, hecho que ha sido una constante en otros estudios publicados con anterioridad 18 , 19 , 20 . En el grupo tratado con estatinas se incluyeron pacientes de mayor edad, preferentemente varones y con una mayor prevalencia de comorbilidades en las esferas cardiovascular, renal, broncopulmonar y neoplásica.…”
Section: Discussionunclassified
“…Hasta la fecha, se han publicado más de 40 estudios observacionales y varios metaanálisis que han intentado discernir si el tratamiento con estatinas pudiese tener un efecto pronóstico positivo en pacientes con COVID-19 6 , 18 , 19 , 20 , 21 . Los metaanálisis publicados presentan una significativa heterogeneidad en cuanto al tipo de estudios y pacientes que se incluyeron y a su metodología; cabe destacar además, que la validez de alguno de ellos 13 se ha cuestionado abiertamente 22 .…”
Section: Discussionunclassified
See 2 more Smart Citations